The role of ego threat in professional growth: Fulfilling the ethical intentions of the SEED Model - Gregory, Jess L.; Mebane, Karreem A. (Educational Practice and Theory, 2020)
Schools and education in general have made an implicit and, we would assert, explicit promise to society to educate all the children in their care. Unfortunately, there are achievement gaps that illustrate how schools have broken this promise. Teacher evaluation and other accountability measures have been heralded as the answer to this problem. Educator ego threat impedes the implementation of goal-driven teacher evaluation models and, thus, ethical questions arise. To realize the noble goals of educator evaluation, leaders must attend to ethical concerns and to the human aspects of ego threat.
0 citations (Crossref) [2023-10-31] tex.ids: gregoryRoleEgoThreat2020a tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85090739249 type: Article
Keywords: Educational leadership; Ego threat; Goal-setting models; Teacher evaluation; Teacher performance; dept.edl; dept.rec; peer-reviewed

The Situation With Modern Leadership Stacking: Racial Politics, Racial Discourse, and the Realities for Black American Coaches—Who Keeps Moving the Goalposts? - Harrison, C.; Mebane, Karreem; Fennell, Marcis; Griffin, Whitney; McAllister, Dre; Hart, Richard; McArdle, Danielle (Kinesiology Review, 2025)
Keywords: Black male; Gender studies; Law; NFL hiring practices; Political science; Politics; Psychology; Race (biology); Racial bias; Rooney Rule; Social psychology; Sociology; coaching pipeline; dept.rec; peer-reviewed; racial stacking